Legal Consequences of Operating an Unlicensed Vocational Training Institution in Bali - Ni Ketut Ratna Vitri Wijayanti; I Nyoman Suandika; Kadek Dedy Suryana (Yayasan Adra Karima Hubbi, 2024)
Background. Non-formal education organized for people who need provision of knowledge, skills, life skills, and attitudes to develop themselves, develop a profession, work, independent business, and / or continue their education to a higher level. Purpose. This thesis aims to analyze the legal consequences and legal processes that Courses and Training Institutions are one form of unit taken from carrying out unlicensed job training institutions in Bali. Method. This research is conducted with normative legal research method, namely through literature study of laws and regulations related to vocational training institutions and their operational licenses. Results. The results of this research are expected to provide a clear understanding of the legal consequences that can arise from misusing the work training institute license given by the Government to the work training institute in Bali, where the discussion of legal consequences and what legal process will be taken when the parties feel harmed as a result of the work training institute carrying out activities without a license in Bali. Conclusion. As well as knowing how to seek permission to legalize the operational license of a vocational training institution so that the training institution can be said to be legal. And can be a job training institution for people who need provision of knowledge skills and life skills, to develop themselves, develop their profession, work independently. Job Training Institutions also function as educational services that function as substitutes, additions, or complements to formal education in order to support education in school.Where in Government Regulation Number 5 of 2021 concerning this PP, regulates Business Licensing based on the level of risk of business activities.